2008
DOI: 10.1007/s12284-008-9021-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Rice Genome Sequence to Understand the Molecular Basis of Genome Evolution

Abstract: Accurate sequencing of the rice genome has ignited a passion for elucidating mechanism for sequence diversity among rice varieties and species, both in proteincoding regions and in genomic regions that are important for chromosome functions. Here, we have shown examples of sequence diversity in genic and non-genic regions. Sequence analysis of chromosome ends has revealed that there is diversity in both sequences and distribution in the region of telomere repeat arrays, from chromosome to chromosome, within a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
0
6
1
Order By: Relevance
“…Recent researches from multiple gene loci reported that the average nucleotide diversity of O. sativa ranged 0.0023∼0.0024 [4,43]. Obviously, the nucleotide diversity of Hd6 gene calculated using 398 bp PCR-amplified sequences from the both populations of O. sativa (π= 0.00016) and its wild relatives of O. rufipogon (π=0.00024) in this study was much lower than that of the above researches (Supplementary Table 3).…”
Section: Genome Diversity Within the Hd6 Regions Of Different Speciescontrasting
confidence: 64%
See 1 more Smart Citation
“…Recent researches from multiple gene loci reported that the average nucleotide diversity of O. sativa ranged 0.0023∼0.0024 [4,43]. Obviously, the nucleotide diversity of Hd6 gene calculated using 398 bp PCR-amplified sequences from the both populations of O. sativa (π= 0.00016) and its wild relatives of O. rufipogon (π=0.00024) in this study was much lower than that of the above researches (Supplementary Table 3).…”
Section: Genome Diversity Within the Hd6 Regions Of Different Speciescontrasting
confidence: 64%
“…In plants, the alcohol dehydrogenase gene (Adh1) has been reported to be one of the most highly conserved genes [10,11,41]. For comparison, we also sequenced and calculated Ka and Ks from the coding sequences of Adh1 between all the species used in this study [38] and found a Ka value ≤0.013 and a Ka/Ks ratio ≤0.605. This demonstrates that the nonsynonymous substitution rate in Hd6 is even slower than that in Adh1.…”
Section: Molecular Evolution Of Hd6mentioning
confidence: 96%
“…Although BAC libraries have been constructed from various rice cultivars for the purpose of gene isolation, BAC physical maps covering the whole genome have been reported only in indica ‘Teqing’ and japonica ‘ZH11’ (Tao et al ., ; Wu et al ., ; Lin et al ., ). The ‘Kasalath’ MTP BAC clones and the accompanying map information provide not only genomic resources for confirming gene functions directly through complementary transformation with candidate BACs of interest, but also provide valuable tools to demonstrate the diversity of chromosomal structures between the two rice cultivars in a given genomic region.…”
Section: Discussionmentioning
confidence: 99%
“…A similarity analysis of genomic sequences within large indel sites was performed by BLAST search against the following public databases: the Oryza Repeat Database, containing rice repetitive sequences (http://rice.plantbiology.msu.edu/annotation_oryza.shtml), KOME, containing rice full‐length cDNA sequences (http://cdna01.dna.affrc.go.jp/cDNA/), and the NCBI non‐redundant protein database (ftp://ftp.ncbi.nlm.nih.gov/blast/db/) on demand. Characterization of TE elements within the large indel sites was performed as described previously (Ma et al ., ; Wu et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…W1588, Cameroon). The close genetic relationships of the cultivated rices with their wild ancestors have been confirmed both at the gene level [41][42][43] and at a population structure level, as analysed by using genome-wide retrotransposon markers (in preparation). BAC libraries of each cultivar or accession were constructed as described before 41,44 .…”
Section: Differences Between Amplifiable and Difficult-to-amplify R-gmentioning
confidence: 93%